Lessons learnt about implementing LEGO based therapy (Play Brick Therapy) based on fidelity data and experience from a large school-based randomised controlled trial - Katie Biggs; Gina Gomez de la Cuesta; Ellen Kingsley; Jean McPherson; Fergus Murray; Margaret Laurie; Matt Bursnall; Elizabeth Coates; Amy Barr (PLoS ONE, 2026)
Introduction LEGO® based therapy, a social skills program for autistic children and young people, involves collaborative LEGO® building with adult guidance. This paper examines how well the program was delivered in a recent school randomised controlled trial and explores areas for improvement in implementation. The main trial results are published elsewhere. Methods The I-SOCIALISE trial investigated LEGO® based therapy for autistic children in schools. Researchers recruited 98 schools and randomly assigned them to deliver LEGO® based therapy or usual care. LEGO® based therapy sessions lasted one hour per week for 12 weeks with groups of 3 children. Schools received a 3-hour training session and a manual. Researchers measured fidelity to the LEGO® based therapy programme using self-reported checklists and video analysis. Research team insight and experience of the delivery of the training and intervention are included in this paper. Results LEGO® based therapy was delivered to autistic children in schools with high fidelity according to facilitators and independent reviewers. Most groups (69%) received all 12 sessions, and nearly all groups received the minimum dose of 6 sessions (93%). Sessions typically lasted about an hour and had 1–2 autistic children. Facilitators were mostly teaching assistants with moderate experience in autism. Over 90% of sessions included core elements like group building and social interaction. There were disagreements between facilitators and reviewers on adherence to some program elements like rewards and discussing roles. Discussion LEGO® based therapy was delivered with high fidelity in a large school trial, but there were areas for improvement, such as facilitator training and focus on social interaction for and between children. The authors suggest that facilitators may have been more focused on completing LEGO® builds than on facilitating meaningful social interaction and play between children. Three hours of training may not have been enough to prepare facilitators for their role. The study also did not capture young people’s experience of the program, which is important for understanding its effectiveness and impact. Future research should explore how to better measure these aspects and develop a stronger theory of how LEGO® based therapy works.